2021
DOI: 10.1080/13561820.2021.1935810
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of interprofessional collaboration in complementary medicine to develop an educational module “complementary and integrative medicine” for undergraduate students: A mixed-methods study

Abstract: As use of complementary medicine (CM) is increasing, health professionals may require proper training in CM to offer evidence-based advice to their patients. The aim of this study was to explore interprofessional collaboration (IPC) in CM in order to gain a comprehensive overview of determinants and to facilitate the definition of objectives for an undergraduate interprofessional educational module. Pursuant to a sequential mixed-methods approach, focus groups and individual interviews with health professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…The domains and definitions of IPC competencies obtained from qualitative methods from all stakeholder coverage at the national, regional, and provincial levels were appropriate for the primary care system in Thailand. A two-stage sequential mixed method in designing an instrument of this study is consistent with the study in health professional from four different hospitals in Japan [ 47 ], health, medical, welfare, and education field in Japan [ 29 ], and undergraduate student in complementary medicine in Germany [ 48 ]. The approach led to understand the working environment of collaborative practice in DHS of the specific context in Thailand.…”
Section: Discussionsupporting
confidence: 62%
“…The domains and definitions of IPC competencies obtained from qualitative methods from all stakeholder coverage at the national, regional, and provincial levels were appropriate for the primary care system in Thailand. A two-stage sequential mixed method in designing an instrument of this study is consistent with the study in health professional from four different hospitals in Japan [ 47 ], health, medical, welfare, and education field in Japan [ 29 ], and undergraduate student in complementary medicine in Germany [ 48 ]. The approach led to understand the working environment of collaborative practice in DHS of the specific context in Thailand.…”
Section: Discussionsupporting
confidence: 62%
“…They concluded that an interprofessional approach could help to overcome stereotypes. Prill et al conducted a mixed method study about interprofessional teaching regarding CIM and their participants emphasized the relevance of team meetings as a factor promoting interprofessional collaboration ( 55 ). This could also be relevant for university hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on integrative medicine and complementary care, have shown that despite controversies and challenges in terms of evidence, there is good chance for fostering interprofessional collaboration with mainstream medical practices. This might mean de ning and clari cation on speci cs related to TBS intervention, communication to reach an equal understanding with practitioners and education of shared professional competencies (49,50).…”
Section: Discussionmentioning
confidence: 99%